2015
DOI: 10.1111/ijsa.12118
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Job Relatedness and Self‐efficacy in Applicant Perceptions of Fairness in a High‐stakes Selection Setting

Abstract: AQ1 8This article presents results from two samples of applicants (total N 5 368) for general prac-

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 68 publications
(189 reference statements)
0
6
0
Order By: Relevance
“…For example, Schleicher et al (2006) found that opportunity to perform had a different relationship with fairness depending on whether it was measured before or after feedback, and Walker, Bauer, Cole, Bernerth, Feild, and Short (2013) found that justice differentially affected organizational attractiveness at different points in the recruitment process. Similarly, Zibarras and Patterson (2015) found that job relatedness measured pre- and postfeedback differentially predicted fairness. In other words, the research to date suggests that applicant reactions are dynamic in nature, and when they are measured in the selection process can affect reactions as well as their correlates.…”
Section: Addressing the “What’s New?” Question: An Updated Model Of Amentioning
confidence: 91%
“…For example, Schleicher et al (2006) found that opportunity to perform had a different relationship with fairness depending on whether it was measured before or after feedback, and Walker, Bauer, Cole, Bernerth, Feild, and Short (2013) found that justice differentially affected organizational attractiveness at different points in the recruitment process. Similarly, Zibarras and Patterson (2015) found that job relatedness measured pre- and postfeedback differentially predicted fairness. In other words, the research to date suggests that applicant reactions are dynamic in nature, and when they are measured in the selection process can affect reactions as well as their correlates.…”
Section: Addressing the “What’s New?” Question: An Updated Model Of Amentioning
confidence: 91%
“…Withholding the presence of AIE in the selection process may not only lead to applicants selecting out when this information is discovered but also tamper any signaling benefits arising from its use. Organizations should also clearly explain the link of AIE to the job and organization early in the process, as well as make efforts to engage applicants in other aspects of the company identity (A. M. Ryan et al., 2000; Zibarras & Patterson, 2015). Such increased engagement early on can reinforce the correct signaling properties of the AIE and potentially maintain high‐quality, curious job seekers in the applicant pool.…”
Section: Discussionmentioning
confidence: 99%
“…Given their ability to generate humor, we expect people with high humor production to be more confident in a job interview context when presented with humorous interview questions. Past research has found that the applicant's confidence is associated with their motivation and anxiety on employment tests (Bauer et al, 1998;Zibarras & Patterson, 2015). For these reasons, we expect job seekers who are high on humor production to be more motivated and report less anxiety toward responding to OPQs for a job interview.…”
Section: Study 2: Jobseeker Sense Of Humormentioning
confidence: 92%